Comparison of the Serum Concentrations of Micronutrients Zinc and Iron in Epileptic Children before and after Administration of Valproic ACID - Ratih Dwi Andini1 , Darto Saharso2 , Roedi Irawan2 , Prastiya Indra Gunawan2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: The mortality rate of epileptic patients has increased despite advances in the treatment ofepilepsy. Several studies have indicated that changes of micronutrient homeostasis led to seizures. Theanticonvulsant valproic acid affects the intracellular concentration of micronutrients.Objective: To compare the serum concentrations of micronutrients zinc and iron in paediatric patients withepilepsy before and after administration of valproic acid.Method: A prospective cohort design study was conducted in children with epilepsy from July to December2019 in the outpatient department of paediatric neurology, Dr. Soetomo Regional Public Hospital, Surabaya,Indonesia. Serum concentrations of micronutrients zinc and iron were measured using the colorimetricmethod. Statistical analysis used paired t-test with p<0.05 being considered significant.Results: The study sample comprised 20 children with epilepsy. There were 13 (65%) males. Eight (40%)children were in the 1-5 year age group. Seizure type was generalised in 18 (90%) patients. The mean serumiron concentrations before and after valproic acid treatment were 23.9±16.8 µmol/L and 25.8±16.4 µmol/Lrespectively (p=0.700). The mean serum zinc concentrations before and after valproic acid treatment were13±16.8 µmol/L and 26.8±15.4 µmol/L respectively (p=0.004).Conclusions: There was a statistically significant increase in the mean serum zinc concentration aftervalproic acid treatment in children with epilepsy. There was however no statistically significant increase inthe mean serum iron concentration after valproic acid treatment in children with epilepsy.